Kajian Literatur Sistematis Faktor Psikososial yang Berhubungan dengan Risiko Psikososial pada Pekerja - Tresnawati, Lena; Erwandi, Dadan (Health Information : Jurnal Penelitian, 2021)
Stress is a form of psychosocial risk, those physical and mental responses due to an imbalance between demands and abilities. Apart from job factors, stressors can be form in individual, social, and family factors. The are many people who not realize their psychosocial symptoms arise. The study aims to analyze factors associated with psychosocial risk in the workplace. This study is a systematic review with Preferred Reporting Items for Systematic Reviews & Meta Analyses (PRISMA) method. The database used to search data and information is PubMed and Science Direct. The keywords used during the search process are work stress, job stress, mental health, occupational stress, work conflict, and psychosocial risk. There were 244 studies in the initial search, but only 25 studies met the criteria. Factors associated with psychosocial risk of workers are gender, education level, work pressure, social support, physical activity, working hours, job satisfaction, and family-work conflict.